The brake pressure change rate in brake chamber and its online monitoring in semitrailer transport vehicle for dangerous cargo. (May 2023) - Zhao, Ran; Li, Gangyan; Yu, Bing; Yang, Fan
The electronically controlled pneumatic brake system (ECPBS) of semitrailer transport vehicle for dangerous cargo (STVDC) is required to control the brake pressure in each brake chamber accurately and stably. Accordingly, the brake pressure change rate (BPCR) in the brake chamber is taken as one of the evaluation parameters and control indicators of ECPBS for STVDC in this paper; an online monitoring implementation scheme of the BPCR in the brake chamber is designed; a simplified model is built based on AMESim and verified by hardware-in-the-loop experiments based on dSPACE; finally, the online monitoring function of BPCR in the brake chamber is validated with the simplified model. This paper provides a new idea for the design and development of ECPBS for STVDC.